BASIS DAN DIMENSI ATAS PADA GRAF PEMBAGI NOL DARI RING KOMUTATIF - Inne Syafrian Putri; Bintang Puja Rahayu (Jurnal Matematika dan Sains (JMS), 2022)
Let  be the set of nonzero divisors of the commutative ring . The zero divisor graph of  is  with the set of vertices , where two distinct vertices  and  are neighbors if and only if . The value of the upper dimension and the minimum solution set (base) of the zero divisor graph  is finite. The steps to find the upper dimensions and base are from the specified ring, determine the zero divisor graph of the ring, and look for a different representation of . The set  is called the solution set if all the vertices of  have different representations of . In this study, some theorem about upper dimensions and base of the zero divisor graph of the commutative ring are discussed.